EZH2 and KDM6A Act as an Epigenetic Switch to Regulate Mesenchymal Stem Cell Lineage Specification - Sarah Hemming; Dimitrios Cakouros; Sandra Isenmann; Lachlan Cooper; Danijela Menicanin; Andrew C.W. Zannettino; Stan Gronthos (2013)
The methyltransferase, Enhancer of Zeste homology 2 (EZH2), trimethylates histone 3 lysine 27 (H3K27me3) on chromatin and this repressive mark is removed by lysine demethylase 6A (KDM6A). Loss of these epigenetic modifiers results in developmental defects. We demonstrate that Ezh2 and Kdm6a transcript levels change during differentiation of multipotential human bone marrow-derived mesenchymal stem cells (MSC). Enforced expression of Ezh2 in MSC promoted adipogenic in vitro and inhibited osteogenic differentiation potential in vitro and in vivo, whereas Kdm6a inhibited adipogenesis in vitro and promoted osteogenic differentiation in vitro and in vivo. Inhibition of EZH2 activity and knockdown of Ezh2 gene expression in human MSC resulted in decreased adipogenesis and increased osteogenesis. Conversely, knockdown of Kdm6a gene expression in MSC leads to increased adipogenesis and decreased osteogenesis. Both Ezh2 and Kdm6a were shown to affect expression of master regulatory genes involved in adipogenesis and osteogenesis and H3K27me3 on the promoters of master regulatory genes. These findings demonstrate an important epigenetic switch centered on H3K27me3 which dictates MSC lineage determination.